Critical Thinking Skills of Slow Learners in Mathematical Problem-Solving: A Systematic Literature Review - Sulfiati; Irwan Akib; Muhammad Muzaini (Journal of Mathematics Instruction, Social Research and Opinion, 2025)
Although much research has highlighted slow learners' difficulties in learning mathematics, most studies have focused only on the final learning outcomes without delving into the thinking processes during problem-solving. The lack of research on the cognitive steps slow learners take to develop critical thinking skills creates a gap in the literature that needs to be filled. The article examines the connection between the "critical thinking ability of slow learner students" and "solving mathematical problems." We recommend using the PRISMA flowchart article selection steps for systematic literature reviews. This systematic literature review investigates the critical thinking skills of slow learners in mathematical problem-solving. We screened 756 studies using the PRISMA framework, which yielded 8 relevant articles. Findings identify four main categories of errors (conceptual, principled, algorithmic, and computational) commonly encountered by slow learners, emphasising the necessity of tailored teaching methods and technological interventions. Clinical teaching is crucial for guiding slow learners through their educational journey. Recommendations include employing open-ended tasks and integrating real-world problems to develop critical thinking skills effectively. The study offers valuable insights for educators and curriculum developers aiming to enhance inclusive mathematics education.